Contralateral Dorsally Based Septal Mucoperichondrial Page Flap, for Nasal Lining Reconstruction. Issue 4 (June 2015) - Collins, James B.; Czerwinski, Marcin
<x xml:space="preserve">Abstract</x> Background: Although excellent techniques for reconstruction of nasal cover and support have been described, reconstruction of large nasal lining defects remains a challenge. Currently available methods have several shortcomings including limited size, airway obstruction, need for multiple procedures, and creation of septal fistulae. Methods: We present 2 cases of nasal lining reconstruction for the lower and mid nasal vaults using a contralateral dorsally based septal mucoperichondrial page flap transposed dorsal to nasal septum and superficial to the ipsilateral upper lateral cartilage. Appropriate, uncomplicated, reconstruction of nasal lining was confirmed in both cases. Discussion: In the lower vault, the flap permits a single-stage reconstruction, without obstruction of the external nasal valve or compromise of caudal septal support. In the mid-vault, the flap allows for reconstruction without creation of a septal fistula or narrowing of the internal nasal valve. In both locations, the size of the flap may be increased by extending it onto nasal floor, and support may be added by combining the flap with septal cartilage. Conclusion: The contralateral dorsally based septal mucoperichondrial flap is a useful option for reconstruction of lower and mid nasal vault lining defects.